Needs Analysis for the Development of Contextual Card Media to Enhance Understanding of Ecosystem Harmony in Fifth-Grade Elementary Students - Febrianasari, Ria; Susantini, Endang; Suryanti, Suryanti (Papanda Publisher, 2025)
This study aims to analyze the needs and design a contextual card-based learning medium to improve the understanding of ecosystem harmony concepts among fifth-grade elementary students. The research employed a Research and Development (R&D) approach, with the initial stage focusing on needs analysis through observations, interviews, and diagnostic tests. The results indicated that students had difficulties understanding the relationships among ecosystem components, the concept of food chains, and environmental balance. Teachers reported limited availability of relevant instructional media, while literature reviews confirmed the effectiveness of visual-interactive media in enhancing science concept comprehension among elementary students. The proposed card media incorporates structured information, engaging illustrations, and interactive activities tailored to students’ cognitive development levels. This design is expected to serve as an alternative solution in science learning, linking abstract concepts with real-world phenomena in students’ surroundings. Further research is recommended to evaluate the feasibility and effectiveness of the media in improving student learning outcomes.